(untitled) (Revista Contexto & Educação, 2022)
This article aims to discuss teacher formation for technological professional education (EPT) from a historic perspective, in its first manifestations and the challenges faced in this historic moment. This framework is built with the intention of revealing the reality evidenced in discussions about the formation of teachers in the context of EPT, in which, since their original formation, they see themselves far from theoretical concepts that discuss the world of work and its intrinsic relation to the world of education. Added to that, public policies are still insufficient for the adequate continuous formation, intensified nowadays in our country, with policies that devalue education in general. Besides, the offered actions are mostly fast and fragmented for a constant diagnosis of the need for qualification and appreciation of these professionals. It is in this scenery that the teacher, characterized as a worker who needs a solid formation, is routinely challenged to ensure a solid and whole human construction to their students, a formation that overcomes the mere adhesion to the needs of an increasingly exploratory market in this historic moment.